2016
DOI: 10.1177/1078155216665244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single agent high-dose methotrexate-related acute kidney injury on length of hospitalization and relative dose intensity in adult patients with central nervous system lymphoma

Abstract: Purpose Grade ≥3 adverse effects prolong hospitalization and reduce chemotherapy dose intensity. The purpose of this study was to evaluate the rate and severity of high-dose methotrexate-related acute kidney injury and analyze its effect on hospital length of stay and relative chemotherapy dose intensity. Methods This was a retrospective cohort analysis. Patients receiving ≥1 dose of high-dose methotrexate were analyzed for acute kidney injury and length of stay. Patients receiving ≥6 cycles of induction thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…We found that AKI significantly increased LOS from 4 days with no AKI to 13 days with AKI grade 3 ( P < .001). These replicate the findings by Steward et al, 21 who reported an almost three-fold increase in LOS comparing AKI grade 3 versus lower grades of AKI, with the mean LOS rising from 5 days to 14 days. May et al 5 reported similar results with a mean LOS of 5.6 days with no renal toxicity compared with 8.9 days with grade ≥ 2.…”
Section: Discussionsupporting
confidence: 89%
“…We found that AKI significantly increased LOS from 4 days with no AKI to 13 days with AKI grade 3 ( P < .001). These replicate the findings by Steward et al, 21 who reported an almost three-fold increase in LOS comparing AKI grade 3 versus lower grades of AKI, with the mean LOS rising from 5 days to 14 days. May et al 5 reported similar results with a mean LOS of 5.6 days with no renal toxicity compared with 8.9 days with grade ≥ 2.…”
Section: Discussionsupporting
confidence: 89%
“…Methotrexate (MTX) is a folate antagonist and cytotoxic chemotherapeutic drug commonly used in the management of malignancies specifically lymphoblastic leukemia, osteosarcoma, and tumors of the head and neck. 1,2 Unfortunately, the efficacy and usefulness of most chemotherapeutic drugs are associated with side effects due to their detrimental effects on both cancerous and normal cells. Specifically, the clinical use of MTX reportedly elicits hematological disorder, myelosuppression, hepatotoxicity, [3][4][5][6] and nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of AKI was higher pre-protocol compared to reported rates in the literature. 36 Post-protocol implementation, the rate of AKI decreased to better reflect literature findings. Results were presented to providers who communicated their support and satisfaction.…”
Section: Discussionmentioning
confidence: 70%
“…3 AKI has been reported in 2–12% of oncology indications. 36 AKI delays methotrexate clearance resulting in complications including cytopenia, hepatotoxicity, mucositis, neurotoxicity, and pulmonary toxicity. 7 Before implementing supportive care measures, life-threatening methotrexate-induced toxicity was around 10% with 4.6–6% mortality rate.…”
Section: Introductionmentioning
confidence: 99%